2016
DOI: 10.1097/md.0000000000004489
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative albumin level following total knee arthroplasty is associated with acute kidney injury

Abstract: Hypoalbuminemia has been reported to be an independent risk factor for acute kidney injury (AKI). However, little is known about the relationship between the albumin level and the incidence of AKI in patients undergoing total knee arthroplasty (TKA). The aim of our study was to assess incidence and risk factors for AKI and to evaluate the relationship between albumin level and AKI following TKA.The study included a retrospective review of medical records of 1309 consecutive patients who underwent TKA between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Kim et al [15] conducted a retrospective study enrolling 4718 patients who underwent partial or total gastrectomy for gastric cancer, and they revealed that patients with preoperative hypoalbuminemia, defined as <40 g/L, had a significantly increased risk for AKI (OR 1.4; 95% CI 1.11-1.77). In patients following hip fracture surgery or total knee arthroplasty, after adjustment for confounders, early postoperative hypoalbuminemia has been shown to be strongly associated with AKI with a cutoff value of <29 g/L and <30 g/L [16,17] [18]. The finding from our study that preoperative hypoalbuminemia had a significant relationship with postoperative AKI was consistent with the results above.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kim et al [15] conducted a retrospective study enrolling 4718 patients who underwent partial or total gastrectomy for gastric cancer, and they revealed that patients with preoperative hypoalbuminemia, defined as <40 g/L, had a significantly increased risk for AKI (OR 1.4; 95% CI 1.11-1.77). In patients following hip fracture surgery or total knee arthroplasty, after adjustment for confounders, early postoperative hypoalbuminemia has been shown to be strongly associated with AKI with a cutoff value of <29 g/L and <30 g/L [16,17] [18]. The finding from our study that preoperative hypoalbuminemia had a significant relationship with postoperative AKI was consistent with the results above.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we assumed that preoperative hypoalbuminemia might be associated with an increased risk of AKI following non-cardiac surgery. However, limited data are currently available on this topic [15][16][17][18]. Thus, this study aimed to investigate the association between preoperative serum albumin concentration and AKI occurrence in high-risk patients following non-cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this fact and our findings, it appears that the pharmacology and ADE of enoxaparin might be enhanced by hypoproteinemia. Additionally, hypoalbuminemia is a major complication after surgery, including TKA [2527]. Kumar et al [28] reported that hypoproteinemia is a risk factor for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers of inflammation, including C-reactive protein (CRP), eosinophil count, and white blood cell count, indicate the degree of inflammation, which can be adjusted for in multivariate analyses. Lee et al [50, 51] adjusted for C-reactive protein (CRP) and the result showed that preoperative albumin levels were associated with AKI, the same result as in studies that have not adjusted for CRP [5255]. Thus, evidence suggests that hypoalbuminemia is a significant independent predictor of both AKI and death following AKI.…”
Section: Risk Factorsmentioning
confidence: 97%
“…In human clinical evidence, hypoalbuminemia has been reported to be independently associated with an increased risk of AKI in various surgical and other situations [5055]. A meta-analysis also evaluated the influence of serum albumin levels on the incidence of AKI and mortality in patients with AKI [56].…”
Section: Risk Factorsmentioning
confidence: 99%